X-ray Lithography on Perovskite Nanocrystals Films: From Patterning with Anion-Exchange Reactions to Enhanced Stability in Air and Water - Palazon, Francisco (ACS Nano, 2015)
[Image: see text] Films of colloidal CsPbX(3) (X = I, Br or Cl) nanocrystals, prepared by solution drop-casting or spin-coating on a silicon substrate, were exposed to a low flux of X-rays from an X-ray photoelectron spectrometer source, causing intermolecular C=C bonding of the organic ligands that coat the surface of the nanocrystals. This transformation of the ligand shell resulted in a greater stability of the film, which translated into the following features: (i) Insolubility of the exposed regions in organic solvents which caused instead complete dissolution of the unexposed regions. This enabled the fabrication of stable and strongly fluorescent patterns over millimeter scale areas. (ii) Inhibition of the irradiated regions toward halide anion exchange reactions, when the films were exposed either to halide anions in solution or to hydrohalic vapors. This feature was exploited to create patterned regions of different CsPbI(x)Br(y)Cl(z) compositions, starting from a film with homogeneous CsPbX(3) composition. (iii) Resistance of the films to degradation caused by exposure to air and moisture, which represents one of the major drawbacks for the integration of these materials in devices. (iv) Stability of the film in water and biological buffer, which can open interesting perspectives for applications of halide perovskite nanocrystals in aqueous environments.